Padalang tinig - Castillo, Nicole Ann
The film is about the sacrifice of an eldest daughter in order to fulfill her responsibilities to her family. Lourdes sacrificed her own goals in order to take care and send her younger sister, Lima to school. Now Lourdes feels upset. Upset, because she feels that she cannot carry out her goals anymore. She feels that she cannot get out of that cycle of responsibilities vested on her. Because Lima decided to support her child, Margaret by living the country, while leaving her daughter with Lourdes.